2012
DOI: 10.1063/1.3691193
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of parahydrogen induced longitudinal two-spin order to evenly distributed single spin polarisation by optimal control pulse sequences

Abstract: Strongly enhanced spin polarization in the form of longitudinal spin order can be generated on target molecules by using parahydrogen in a catalyzed hydrogenation reaction. An optimal control algorithm was used to generate radiofrequency pulse sequences which convert the arising longitudinal two-spin order into single-spin Zeeman order with high efficiency and distribute it evenly between three coupled spins within the same molecule. The pulses are designed to be very robust towards variations in the B(0) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…13 At the same time, in many CIDNP and PHIP applications it is highly desirable to have molecules with considerable net hyper-polarization, which can be difficult to achieve, for instance, by manipulating the ALTADENA or PASADENA pattern by NMR pulse sequences. Although there are successful examples of utilizing NMR pulses to control and transfer PHIP-derived spin order 5,7,[14][15][16][17][18] the need for precise synchronization of the pulses with the chemical reaction and control of coherences between the spin states can be a problem. To have at the output net hyper-polarization is especially crucial for MRI since at typical magnetic fields used in the MRI technique NMR multiplet structures as well as chemical shifts cannot be resolved with the consequence that only the integral net hyper-polarization is observable.…”
Section: Introductionmentioning
confidence: 99%
“…13 At the same time, in many CIDNP and PHIP applications it is highly desirable to have molecules with considerable net hyper-polarization, which can be difficult to achieve, for instance, by manipulating the ALTADENA or PASADENA pattern by NMR pulse sequences. Although there are successful examples of utilizing NMR pulses to control and transfer PHIP-derived spin order 5,7,[14][15][16][17][18] the need for precise synchronization of the pulses with the chemical reaction and control of coherences between the spin states can be a problem. To have at the output net hyper-polarization is especially crucial for MRI since at typical magnetic fields used in the MRI technique NMR multiplet structures as well as chemical shifts cannot be resolved with the consequence that only the integral net hyper-polarization is observable.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it was shown that the initial longitudinal two-spin order arising from the hydrogenation reaction can be equally distributed between several spins and converted into detectable magnetization [408].…”
Section: State Of the Artmentioning
confidence: 99%
“…Specifically, the derivations of Eqs. (25) and (26), and further details of Eqs. (27) and (28) are given in the supplementary material, 42 Sec.…”
Section: F Krotov-bfgsmentioning
confidence: 99%
“…(25) and (26) is not evaluated. We note that the Hessian matrices, which initially are the N × N identity matrices, in accord with the original BFGS method also require an update,…”
Section: F Krotov-bfgsmentioning
confidence: 99%
See 1 more Smart Citation